Local Repressor AcrR Regulates AcrAB Efflux Pump Required for Biofilm Formation and Virulence in Acinetobacter nosocomialis - Subhadra, Bindu; Kim, Jaeseok; Kim, Dong Ho; Woo, Kyungho; Oh, Man Hwan; Choi, Chul Hee (Frontiers in Cellular and Infection Microbiology, 2018)
Multidrug efflux systems contribute to antimicrobial resistance and pathogenicity in bacteria. Here, we report the identification and characterization of a transcriptional regulator AcrR controlling the yet uncharacterized multidrug efflux pump, AcrAB in Acinetobacter nosocomialis. In silico analysis revealed that the homologs of AcrR and AcrAB are reported in the genomes of many other bacterial species. We confirmed that the genes encoding the AcrAB efflux pump, acrA and acrB forms a polycistronic operon which is under the control of acrR gene upstream of acrA. Bioinformatic analysis indicated the presence of AcrR binding motif in the promoter region of acrAB operon and the specific binding of AcrR was confirmed by electrophoretic mobility shift assay (EMSA). The EMSA data showed that AcrR binds to −89 bp upstream of the start codon of acrA. The mRNA expression analysis depicted that the expression of acrA and acrB genes are elevated in the deletion mutant compared to that in the wild type confirming that AcrR acts as a repressor of acrAB operon in A. nosocomialis. The deletion of acrR resulted in increased motility, biofilm/pellicle formation and invasion in A. nosocomialis. We further analyzed the role of AcrR in A. nosocomialis pathogenesis in vivo using murine model and it was shown that acrR mutant is highly virulent inducing severe infection in mouse leading to host death. In addition, the intracellular survival rate of acrR mutant was higher compared to that of wild type. Our data demonstrates that AcrR functions as an important regulator of AcrAB efflux pump and is associated with several phenotypes such as motility, biofilm/pellicle formation and pathogenesis in A. nosocomialis.